2018
DOI: 10.2478/psicolj-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Priming effects in the recognition of simple and complex words and pseudowords

Abstract: Whether morphological processing of complex words occurs beyond orthographic processing is a matter of intense debate. In this study, morphological processing is examined by presenting complex words (brujería -> brujo –witchcraft -> witch), as well as simple (brujaña->brujo) and complex pseudowords (brujanza ->brujo), as primes in three masked lexical decision tasks. In the first experiment, the three experimental conditions facilitated word recognition in comparison to the control condition, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…However, the evidence of complex pseudo-words activating their stems is limited and is restricted to priming studies (e.g., Hasenäcker, Beyersman, & Schroeder, 2016; Morris et al, 2010; Longtin & Meunier, 2005). In the case of complex pseudo-words, lexical activation cannot be suggested, since pseudo-words are not represented at this level, so the explanation seems to be more reasonable in terms of orthographic or morphological activation at the sublexical (e.g., Lázaro, Illera, & Sainz, 2018) or lemma level (Taft & Nguyen-Hoan, 2010). For instance, in the lemma level, Taft & Nguyen-Hoan (2010) found that the orthographic processing of the input, word, or pseudo-word detects the letters that constitute stems and derivational suffixes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence of complex pseudo-words activating their stems is limited and is restricted to priming studies (e.g., Hasenäcker, Beyersman, & Schroeder, 2016; Morris et al, 2010; Longtin & Meunier, 2005). In the case of complex pseudo-words, lexical activation cannot be suggested, since pseudo-words are not represented at this level, so the explanation seems to be more reasonable in terms of orthographic or morphological activation at the sublexical (e.g., Lázaro, Illera, & Sainz, 2018) or lemma level (Taft & Nguyen-Hoan, 2010). For instance, in the lemma level, Taft & Nguyen-Hoan (2010) found that the orthographic processing of the input, word, or pseudo-word detects the letters that constitute stems and derivational suffixes.…”
Section: Discussionmentioning
confidence: 99%
“…We created three groups of 40 pseudowords each. These groups included polymorphemic pseudowords – pseudowords in which both a stem and a suffix exist as in “footbalist,” suffixed pseudowords – pseudowords in which a real derivational suffix is attached to a non-existing base as in “smopify,” and simple pseudowords – with no stems or suffixes as in “gresmor.” The three lists of pseudowords are matched by first syllable frequency – we matched the pseudowords one by one ensuring that the same first syllable is used to create one pseudoword per condition (see Ferrand et al, 1996), letter length (see e.g., Hudson & Bergman, 1985), and the number of orthographic neighbors – by using the database of Alameda and Cuetos (1995) (e.g., Perea & Pollatsek, 1998); the suffixed and polymorphemic pseudowords are also matched by suffix frequency by pairing the suffixes employed one by one (see for instance Lázaro et al, 2015). The imageability of the pseudowords was scored by 20 university students (16 females, M age = 23, SD = 2.20) through a 7-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…Esto ocurre así en el llamado priming de repetición (casa-casa) cuando hay semejanza ortográfica entre los estímulos inductor y diana (caso-casa) y también cuando ambos guardan una relación morfológica (entiendo-entender) o semántica (marido-mujer) (Forster y Davis 1984; Perea y Gotor 1997;Forster 1998;Sánchez-Casas et al 2003). En cambio, cuando el estímulo inductor es una pseudopalabra (cusa-casa), el efecto de facilitación se desvanece (Lázaro et al 2018) o incluso se hace inhibitorio, es decir, provoca un en enlentecimiento de la respuesta y un mayor porcentaje de errores (Mathey et al 2013).…”
Section: Tareas Conductuales En El Estudio De La Comprensión Del Leng...unclassified